2004
DOI: 10.3201/eid1003.020812
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Changes of Chagas Disease Vector, South America

Abstract: We analyzed the main karyologic changes that have occurred during the dispersion of Triatoma infestans, the main vector of Chagas disease. We identified two allopatric groups, named Andean and non-Andean. The Andean specimens present C-heterochromatic blocks in most of their 22 chromosomes, whereas non-Andean specimens have only 4–7 autosomes with C-banding. These heterochromatin differences are the likely cause of a striking DNA content variation (approximately 30%) between Andean and non-Andean insects. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 20 publications
3
106
0
3
Order By: Relevance
“…2010) and subsequently, post‐Colombian, eastwards into Argentina, Paraguay, Uruguay and Brazil (Panzera et al . 2004; Piccinali et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
“…2010) and subsequently, post‐Colombian, eastwards into Argentina, Paraguay, Uruguay and Brazil (Panzera et al . 2004; Piccinali et al . 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in this ever-changing epidemiologic scenario, new tools exploiting the behaviour and the genetics of T. infestans revealed that wild foci of this species may be much more widespread than previously thought. Moreover, the high genetic diversity observed in a microregion suggests that the Andean Region is the starting point for the dispersion throughout several South American countries (Noireau et al 2000, 2005, Panzera et al 2004). The increasing migration movements and current environmental changes (Briceno-Leon & Galvan 2007) could also favour new passive dispersion processes for the species and the urbanisation of the vectors.…”
Section: Biology Diversity and Strategies For The Monitoring And Conmentioning
confidence: 99%
“…Interestingly, chromosomes are often marked by intraspecific polymorphism in heterochromatic content Panzera et al, 2004). For example, the Andean populations of T. infestans present a 50% higher constitutive heterochromatin content than the non-Andean populations.…”
Section: Systematics and Phylogenymentioning
confidence: 99%